Comparison of the efficacy and safety of 755-nm picosecond alexandrite laser with diffractive lens array vs. fractional microneedle radiofrequency for the treatment of facial photoaging: a retrospective study - Xixin Wu; Houhuang Qiu; Jingchun Chen; Yunkai Zhu; Jialu Xu; Xi Chen; Yutong Wu; Fangfang Wang; Ping Zhong; Qiusheng Lin; Fei Li; John Chen; et al. (Frontiers in Medicine, 2026)
Objective To compare the efficacy and safety of a 755-nm picosecond alexandrite laser combined with a diffractive lens array (PSAL-DLA) vs. fractional microneedle radiofrequency (MNRF) in the treatment of facial photoaging. Methods This retrospective study enrolled 51 patients with facial photoaging (Glogau scale ≥ II), including 22 in the PSAL-DLA group and 29 in the MNRF group. Objective assessments were performed at baseline and within 3 months post-treatment using the VISIA skin analysis system (spots, wrinkles, texture, pores, UV spots, brown spots, red areas, porphyrins). Subjective evaluation was conducted independently by two board-certified physicians using the Modified Fitzpatrick Wrinkle Scale (MFWS) and Global Aesthetic Improvement Scale (GAIS). Analysis of covariance (ANCOVA) was used to compare between-group efficacy, with baseline VISIA scores, age, sex, skin type, and actual follow-up duration as covariates. Treatment-related adverse events were also recorded. Results The PSAL-DLA group demonstrated significant improvements in brown spots and red areas, and the MNRF group showed a significant reduction in pore scores; however, the between-group differences were not statistically significant ( P > 0.05). Notably, the MNRF group exhibited a statistically significant worsening of spots from baseline. ANCOVA revealed that the PSAL-DLA group achieved significantly greater improvements in spots total scores (adjusted means: 82.2 vs. 89.3, P = 0.004) and UV spots (55.4 vs. 59.6, P = 0.022) compared with the MNRF group. Wrinkle improvement correlated positively with baseline severity in both groups. The MNRF group demonstrated a significant within-group improvement in MFWS score, but the between-group comparison with PSAL-DLA showed no significant difference ( P = 0.103). In the GAIS assessment, 68.18% and 72.41% of subjects in the PSAL-DLA and MNRF groups, respectively, were rated as improved or much improved, with no significant between-group difference (P = 0.779). Subgroup analysis revealed no significant interaction between treatment modality and age or skin type ( P > 0.05). Adverse reactions were mainly transient erythema and swelling, with no severe hyperpigmentation or scarring observed. Conclusion Both PSAL-DLA and MNRF are safe and effective for treating facial photoaging. PSAL-DLA appears superior for pigmented indicators (spots, UV spots), while MNRF also demonstrates efficacy for pores and wrinkles, although between-group differences were not significant. Treatment selection should be individualized based on the patient's predominant photoaging manifestations.